Hubungan Antara Durasi Penggunaan Gadget Pada Anak Dengan Sosial Emosional Anak Usia Dini (4-5 Tahun): The Relationship Between Gadget Usage Duration in Children and the Socio-Emotional Development of Early Childhood Children (Ages 4-5) - Ardyansah, Rizki Bahtiyar (Chakra Brahmanda Lentera Institute, 2026)
Background Over time, one thing that is inevitable is the rapid advancement of science and technology, making it accessible to people of all ages around the world. Besides the impact of technological advancements on its users, the use of technology has provided significant benefits to various age groups, especially adults, and even children. This technology includes computers, mobile phones, laptops, and many other types of devices. Gadgets are the most well-known technology among the general public; a gadget is a set of electronic devices used for communication, documentation, social networking, and entertainment. Based on the issues above, the question posed in this study is,